A estatística no futebol: uma análise dos principais fatores que influenciam o número de gols feitos pelos jogadores no campeonato inglês - Mangerona, Robson Alves (Universidade Federal de São Carlos, 2023)
Soccer is considered one of the most popular sports in the world and its relevance is reflected not only in the crowds that fill the stadiums around the 5 continents within the most varied championships, but also proves to be extremely important in the cultural and economic development of a country. Taking this into account, over time, soccer has been a subject of interest for professionals who try, through statistical analysis, to help coaches, managers and, mainly, players find, in numbers, a way to reach their best performances on the field. The objective of this work is, therefore, to analyze and identify which features (total number of shots, shots on goal every 90 minutes, average goal distance of all shots, predicted goals, among others) have the most impact on the number of goals scored by player in a season of Premier League (soccer calendar commonly associated with a total of 38 games played between 20 teams). From this, we want to understand the main factors that influence the final performance of the player, since the number of goals scored by the athletes directly reflects on the performance of a team within the championship.
Statistics in soccer: an analysis of the main factors that influence the number of goals scored by players in the Premier League
Keywords: Número de gols; Campeonato inglês; Regressão binomial negativa; Number of goals; Premier League; Negative binomial regression; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::REGRESSAO E CORRELACAO